THE LATEST TRENDS IN DEVELOPMENT OF DISTANCE EDUCATION IN UKRAINE (Journal of Information Technologies in Education (ITE), 2014)
This article analyzes the current state of distance education in Ukraine and highlights the urgent problems to solve which а new Statute on distance learning has been worked out.
Keywords: distance education; distance learning; electronic educational resources